Monsoonal effects on hydrodynamic and water quality at Setiu wetland, Terengganu - Zuraini Binti Zainol (Universiti Malaysia Terengganu, 2022)
Setiu Wetland is facing shoreline alterations, which caused relocation of the inlet through a natural closing of the old river mouth and the opening of a new one. Research has shown that continuous actions of monsoonal wind, wave, and current were the reason of this alteration. To our knowledge, very few of the previous researches in Setiu Wetland are focusing at the new inlet area. Thus, this study attempts to understand the hydrodynamics and water quality in Setiu Wetland from the new inlet perspective. The repositioning of this inlet raises questions such how the current flow in the lagoon has changed and how capable this ecosystem in maintaining its water quality since most of the sources of anthropogenic activities are situated at the old inlet. In order to have a general overview of the current status at the new inlet, in situ field surveys were carried out during August 2017, December 2017, and February 2018 which represent the southwest monsoon, wet period of northeast monsoon, and dry period of northeast monsoon, respectively. Statistical analysis was performed on the environmental parameters to demonstrate relationships among variables. Numerical modelling was also executed to improve the restrictions of field observations while providing a better understanding of the dynamics of this water body. The results indicated that the current flow in Setiu Wetland is tidally dominated, following the ebb and flood as well as neap and spring tides cycles. Larger size of Setiu River produced slightly stronger tidal current at the south of the inlet area.